2004
DOI: 10.1212/01.wnl.0000127773.72699.c8
|View full text |Cite
|
Sign up to set email alerts
|

Practice Parameter: Medical Treatment of Infantile Spasms

Abstract: Abstract-Objective:To determine the current best practice for treatment of infantile spasms in children. Methods: Database searches of MEDLINE from 1966 and EMBASE from 1980 and searches of reference lists of retrieved articles were performed. Inclusion criteria were the documented presence of infantile spasms and hypsarrhythmia. Outcome measures included complete cessation of spasms, resolution of hypsarrhythmia, relapse rate, developmental outcome, and presence or absence of epilepsy or an epileptiform EEG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
317
2
18

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(346 citation statements)
references
References 64 publications
(159 reference statements)
9
317
2
18
Order By: Relevance
“…Most protocols of ACTH treatment for WS indicate that ACTH should be administered for more than 14 days and then tapered (Yanagaki et al 1999;Mackay et al 2004). Because longer ACTH treatment is associated with more side effects including hypertension, infection, subdural hemorrhage and brain atrophy, some investigators have recommended a shorter duration of ACTH treatment (Ito et al 1990;Hrachovy et al 1994;Kondo et al 2005;Oguni et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Most protocols of ACTH treatment for WS indicate that ACTH should be administered for more than 14 days and then tapered (Yanagaki et al 1999;Mackay et al 2004). Because longer ACTH treatment is associated with more side effects including hypertension, infection, subdural hemorrhage and brain atrophy, some investigators have recommended a shorter duration of ACTH treatment (Ito et al 1990;Hrachovy et al 1994;Kondo et al 2005;Oguni et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…AEDs are typically screened in mature rats that have acute seizures rather than epilepsy and the limited number of animal models for the severe epileptic encephalopathies in children has also been a major hindrance in developing new AEDs [62]. An example of this situation is the case of vigabatrin where it has been shown that the drug is quite successful in the treatment of infantile spasms [63]. This was not predicted by animal models.…”
Section: Developmental Animal Modelsmentioning
confidence: 99%
“…This was not predicted by animal models. Likewise, adrenocorticotrophin hormone (ACTH) has little role in treating seizures in adults, but is quiet effective in the treatment of infantile spasms, an epilepsy syndrome confined to children [63,64].…”
Section: Developmental Animal Modelsmentioning
confidence: 99%
“…No existe tratamiento específico para el SW; sin embargo, el ACTH y la Vigabatrina son las drogas que han dado los mejores resultados (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)34). Lamentablemente estos medicamentos no se encuentran en el petitorio nacional.…”
Section: Introductionunclassified